Thirty-day postoperative outcome of patients with non-traumatic gastroduodenal perforations in southwestern Uganda - Okidi, Ronald; Sambo, Vanusa D.; Ogwang, Martin D.; Mutiibwa, David; Benitez, Noralis P.; Bongomin, Felix (Tropical Doctor, 2020)
We studied our 30-day postoperative outcomes in patients with non-traumatic gastroduodenal perforation (NTGDP) in Mbarara Regional Referral Hospital, southwestern Uganda. We conducted a one-year prospective study of patients who underwent exploratory laparotomy for suspected NTGDP between June 2016 and July 2017. Twenty-nine patients had NTGDP, the male-to-female ratio was 3:1 and median age was 60 years (range¼13–80 years). Most (83%) patients were negative for Helicobacter pylori on histology. One patient had a gastric adenocarcinoma. A total of 26 (90%) patients had Graham’s omentopexy performed. The 30-day mortality rate was 34%. Pyrexia at hospital admission, pre-surgical delay (> 72 h), preoperative shock and peritoneal contamination, were associated with higher mortality rates with preoperative shock being an independent predictor of mortality. H. pylori-negative NTGDP presents a unique challenge in our setting, affecting mainly middle-aged and elderly patients. One-third of our patients did not survive one month.
Keywords: Non-traumatic gastroduodenal perforation; 30-day outcome; Southwestern Uganda